Recurrence and Prognostic Value of Circulating Tumor Cells in Resectable Pancreatic Head Cancer: A Single Center Retrospective Study - Zhang, Qiao; Xia, Feng; Sun, Qiang; Cao, Wenjing; Mo, Ali; He, Weiming; Chen, Jiazhen; Zhang, Weiqiao; Chen, Weiqiang (Frontiers in Surgery, 2022)
ABSTRACT: Backgruond and aim To investigate the effect of anterior circulation tumor cells (CTC) on postoperative recurrence and overall survival prognosis of pancreatic head cancer after pancreaticoduodenectomy (PD). Methods From March 2014 to January 2020, 73 patients with pancreatic head cancer underwent radical resection (R0) in Zhongshan People's Hospital. CTCs in peripheral blood of patients with pancreatic head cancer were detected by Cyttel detector before PD. Seventy-three patients were divided into positive and negative groups according to the positive criteria. The relationship between the clinical data of CTCs and postoperative recurrence, survival and prognosis was explored. Cox proportional hazards model was used to analyze the risk factors affecting the postoperative recurrence of PD and the survival prognosis of patients. Results Of the 73 patients, 41 were in the positive group. Preoperative CTCs were correlated with tumor vascular invasion and preoperative CA199 (P < 0.05), and correlated with postoperative liver metastasis. Preoperative CTCs positivity, lymph node metastasis, vascular invasion and nerve invasion (P < 0.05) were independent risk factors for postoperative tumor recurrence. Preoperative positive CTCs, tumor diameter greater than 2 cm and vascular invasion (P < 0.05) were independent risk factors for survival prognosis of patients. Conclusion The detection of CTCs before pancreatic head cancer surgery is an important factor affecting the postoperative recurrence and survival prognosis of pancreatic head cancer, which is of great significance in guiding clinical work.